Williams Obstetrics - Cunningham, F. Gary; Gant, Norman F.; Leveno, Kenneth J.; Gilstrap III, Larry G.; Hauth, John C.; Wenstrom, Katharine D. (New York McGraw-Hill, 2003)
This volume covers the entire field of obstetrics. With a scientific basis and practical applicability, this work provides illustrations, algorithms, and tables to amplify material presented in the text. Included are chapters on preconception counselling and chronic hypertension.
Include Index.
International Edition.
Keywords: Obstetrics